Study on factor that influence the movement of Petronas Dagangan Berhad (PETDAG) stock price in Bursa Malaysia / Arif Hanafi Mokhtar - Mokhtar, Arif Hanafi (Faculty of Business and Management, 2011)
Purpose – The purpose of this paper is to investigate and study the relationship between the factors that influence stock price with Petronas Dagangan Berhad stock price.